2023
DOI: 10.1186/s12916-023-02988-3
|View full text |Cite
|
Sign up to set email alerts
|

Global impact and cost-effectiveness of one-dose versus two-dose human papillomavirus vaccination schedules: a comparative modelling analysis

Kiesha Prem,
Yoon Hong Choi,
Élodie Bénard
et al.

Abstract: Background To eliminate cervical cancer as a public health problem, the World Health Organization had recommended routine vaccination of adolescent girls with two doses of the human papillomavirus (HPV) vaccine before sexual initiation. However, many countries have yet to implement HPV vaccination because of financial or logistical barriers to delivering two doses outside the infant immunisation programme. Methods Using three independent HPV transm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…We also found that irrespective of the screening coverage, the single-dose 9vHPV vaccination is likely to be more cost-effective compared to the two-dose 9vHPV vaccination under pessimistic assumptions of one-dose 30-year duration of protection, which is generally consistent with previous modeling studies [50,57,58]. Evidence from immunogenicity trials and post-randomization studies has indicated that a single vaccine dose of vaccine may offer comparable long-lasting protection against infection and clinical endpoints as two or three doses [6,17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also found that irrespective of the screening coverage, the single-dose 9vHPV vaccination is likely to be more cost-effective compared to the two-dose 9vHPV vaccination under pessimistic assumptions of one-dose 30-year duration of protection, which is generally consistent with previous modeling studies [50,57,58]. Evidence from immunogenicity trials and post-randomization studies has indicated that a single vaccine dose of vaccine may offer comparable long-lasting protection against infection and clinical endpoints as two or three doses [6,17].…”
Section: Discussionsupporting
confidence: 89%
“…Evidence from immunogenicity trials and post-randomization studies has indicated that a single vaccine dose of vaccine may offer comparable long-lasting protection against infection and clinical endpoints as two or three doses [6,17]. Routine single-dose HPV vaccination will release vaccine doses, enabling a faster expansion of the vaccination scale, and thus achieving the maximum health and economic benefits within the constrained supply in China [58]. In the meantime, it is worth noting that China's pricing for the 9vHPV vaccine is beyond the reach of most eligible women and government-funded programs, prompting future research related to optimal vaccine pricing and price negotiations with manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…In BMC Medicine , Prem and colleagues compared the long-term health benefits and cost-effectiveness of one-dose versus two-dose HPV vaccination in 188 countries, under scenarios in which the one-dose schedule provides either a shorter duration of protection or lower vaccine efficacy compared to two doses [ 6 ]. Prem et al’s study revealed that if a single HPV vaccine dose confers ≥ 30 years of protection or lifelong protection but at 80% efficacy, the difference in population benefits of the one-dose versus two-dose vaccination schedule would be minimal [ 6 ]. Importantly, the study underscored that, in contrast to high-income countries (HICs), the one-dose schedule in LMICs would avert a greater number of cervical cancer cases and necessitate the vaccination of fewer girls per prevented case [ 6 ].…”
Section: Main Textmentioning
confidence: 99%
“…Prem et al’s study revealed that if a single HPV vaccine dose confers ≥ 30 years of protection or lifelong protection but at 80% efficacy, the difference in population benefits of the one-dose versus two-dose vaccination schedule would be minimal [ 6 ]. Importantly, the study underscored that, in contrast to high-income countries (HICs), the one-dose schedule in LMICs would avert a greater number of cervical cancer cases and necessitate the vaccination of fewer girls per prevented case [ 6 ]. This highlights the value of the one-dose program for cervical cancer prevention in LMICs.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation